2020
DOI: 10.52547/nbr.7.3.363
|View full text |Cite
|
Sign up to set email alerts
|

Lonicera japonica, a neglected plant in Persian botanical literature with a review on “Yass” and “Yassaman” in Iran

Abstract: Lonicera japonica is generally known as "Yass" or "Gole Yass" among Iranians, however, this vernacular name is not widely known in Persian botanical textbooks or encyclopedia. Moreover, specialists in plant science and horticulture recognize this plant as "Pich-e Aminoddoleh", which has been already dedicated to another species, Lonicera caprifolium While the terms "Yassaman" and "Yassamin" were such widely used in the classical Persian literature that many scholars believe that the genus Jasminum hasits name … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Linalyl acetate and linalool are key constituents of lavender essential oil, and a study in this regard showed that linalyl acetate similarly affects glutamate receptors to anxiolytics and tranquilizers [12]. Linalyl has also been shown to be one of the main constituents of jasmine, and linalyl acetate has narcotic effects, such as analgesics, hypnotics, and anti-anxiety drugs [13]. Jasmine or jessamine are members of the genus Jasminum, which belongs to the family Oleaceae.…”
Section: Introductionmentioning
confidence: 99%
“…Linalyl acetate and linalool are key constituents of lavender essential oil, and a study in this regard showed that linalyl acetate similarly affects glutamate receptors to anxiolytics and tranquilizers [12]. Linalyl has also been shown to be one of the main constituents of jasmine, and linalyl acetate has narcotic effects, such as analgesics, hypnotics, and anti-anxiety drugs [13]. Jasmine or jessamine are members of the genus Jasminum, which belongs to the family Oleaceae.…”
Section: Introductionmentioning
confidence: 99%